Fractions of Shen-Sui-Tong-Zhi Formula Enhance Osteogenesis Via Activation of β-Catenin Signaling in Growth Plate Chondrocytes - Xu, Rui; Zeng, Qinghe; Xia, Chenjie; Chen, Jiali; Wang, Pinger; Zhao, Shan; Yuan, Wenhua; Lou, Zhaohuan; Lin, Houfu; Xia, Hanting; Lv, Shuaijie; Xu, Taotao; et al. (Frontiers in Pharmacology, 2021)
Background: Shen-sui-tong-zhi formula (SSTZF) has been used to treat osteoporosis for decades and shows excellent clinical efficacy. This article aims to explore the optimal anti-osteoporotic ingredient and its precise mechanisms in mice models. Methods: In this study, we first screened the optimal anti-osteoporosis fraction of SSTZF extract in vivo, and then further explored the mechanism of its effects both in vivo and in vitro. Ten-week-old female C57BL/6J mice were administrated with each fraction of SSTZF. At 10 weeks after ovariectomy (OVX), femurs were collected for tissue analyses, including histology, micro-CT, biomechanical tests, and immunohistochemistry for ALP, FABP4, and β-catenin. Additionally, we also evaluated the mRNA expression level of ALP and FABP4 and the protein expression level of β-catenin after being treated with SSTZF extract in C3H10T1/2 cells. Moreover, we investigated the anti-osteoporosis effect of SSTZF extract on mice with β-catenin conditional knockout in growth plate chondrocytes (β-cateninGli1ER mice) through μCT, histology, and immunohistochemistry analyzes. Results: At 10 weeks after treatment, osteoporosis-like phenotype were significantly ameliorated in SSTZF n-butanol extract (SSTZF-NB) group mice, as indicated by increased trabecular bone area and ALP content, and decreased lipid droplet area and FABP4 content. No such improvements were observed after being treated with other extracts, demonstrating that SSTZF-NB is the optimal anti-osteoporosis fraction. Additionally, the elevated β-catenin was revealed in both OVX mice and C3H10T1/2 cells with SSTZF-NB administered. Furthermore, a significant osteoporosis-like phenotype was observed in β-cateninGli1ER mice as expected. However, SSTZF-NB failed to rescue the deterioration in β-cateninGli1ER mice, no significant re-upregulated ALP and downregulated FABP4 were observed after being treated with SSTZF-NB, demonstrating that SSTZF-NB prevents bone loss mainly via β-catenin signaling. Conclusion: SSTZF-NB enhances osteogenesis mainly via activation of β-catenin signaling in growth plate chondrocytes. SSTZF-NB is the optimal anti-osteoporosis fraction of SSTZF and it can be considered a salutary alternative therapeutic option for osteoporosis.